Enhancing Cooperation in Defence against Terrorism - Tokgöz, Kenan (IOS Press, 2014)
The Centre of Excellence – Defence against Terrorism (COE-DAT) traveled to Astana, Kazakhstan to conduct an advanced training course (ATC) entitled "Enhancing Cooperation in Defense against Terrorism" on 27 September-01 October 2010. A total of eleven experts from five countries helped the participants discuss these issues in order to facilitate interoperability between these countries and NATO in the fight against terrorism. The articles in this book reflect those presentations and discussions.